Parametric investigation and optimisation of mechanical properties of thick tri-material based composite of PLA-PETG-ABS 3D-printed using fused filament fabrication - Imran Khan; Muhammad Tariq; Muhammad Abas; Muhammad Shakeel; Fatima Hira; Ans Al Rashid; Muammer Koç (Composites Part C: Open Access, 2023)
Tri-material and tri-layered composites find numerous applications in the biomedical, aerospace, and automotive industries. However, such composites face challenges when fabricated through conventional methods (Electrospinning, hand lay-up, Film Casting, In-situ polymerization), such as interface bond strength, strength-to-mass ratio, etc. Additive manufacturing can be used to fabricate such composites to overcome these challenges. In this study, tensile samples of tri-material based 3D-printed (TM3DP) polymer composite of polylactic acid (PLA), polyethylene terephthalate glycol (PETG), and acrylonitrile butadiene styrene (ABS) were successfully processed using fused filament fabrication (FFF) for the first time. The composite is fabricated such that 33.333% PLA was printed first, followed by 33.333% PETG, and, in the end, 33.333% ABS so that PETG is sandwiched between PLA and ABS. The effect of FFF processing parameters on the tensile properties of the printed composites was investigated. After preliminary experiments and a literature review, infill density (ID), printing speed (PS), and layer thickness (LT) were selected as the main processing parameters. The tensile strength (TS) and tensile strain (ℇ) were selected as the outputs (responses) of this study. Tensile testing was performed after printing composite tensile samples on Instron Universal Testing Machine (5 KN). An analysis of variance (ANOVA) was also performed to check the significance of FFF process parameters. The results concluded that the selected FFF process parameters were significant in the interaction state of both tensile properties. Scanning electron microscopy (SEM) and optical microscopy were also performed, which indicated that various defects, including micropores, voids, and micro / major delamination occurred in conditions of high LT, high PS, and low ID. This resulted in a low TS of 27.1 MPa and ℇ of 0.5 mm/mm. No major defects were observed under high LT, high PS, and high ID, which resulted in the highest TS of 39.5 MPa and ℇ of 0.95. Finally, optimum conditions were suggested for fabricating the thick TM3DP composite samples, believed to enhance the TS-to-mass ratio by 16.4% compared to the single solid 3D-printed base materials.